TRPV1 Hyperfunction Contributes to Renal Inflammation in Oxalate Nephropathy - Lu, Chien-Lin (Int J Mol Sci, 2021)
Inflammation worsens oxalate nephropathy by exacerbating tubular damage. The transient receptor potential vanilloid 1 (TRPV1) channel is present in kidney and has a polymodal sensing ability. Here, we tested whether TRPV1 plays a role in hyperoxaluria-induced renal inflammation. In TRPV1-expressed proximal tubular cells LLC-PK(1), oxalate could induce cell damage in a time- and dose-dependent manner; this was associated with increased arachidonate 12-lipoxygenase (ALOX12) expression and synthesis of endovanilloid 12(S)-hydroxyeicosatetraenoic acid for TRPV1 activation. Inhibition of ALOX12 or TRPV1 attenuated oxalate-mediated cell damage. We further showed that increases in intracellular Ca(2+) and protein kinase C α activation are downstream of TRPV1 for NADPH oxidase 4 upregulation and reactive oxygen species formation. These trigger tubular cell inflammation via increased NLR family pyrin domain-containing 3 expression, caspase-1 activation, and interleukin (IL)-1β release, and were alleviated by TRPV1 inhibition. Male hyperoxaluric rats demonstrated urinary supersaturation, tubular damage, and oxidative stress in a time-dependent manner. Chronic TRPV1 inhibition did not affect hyperoxaluria and urinary supersaturation, but markedly reduced tubular damage and calcium oxalate crystal deposition by lowering oxidative stress and inflammatory signaling. Taking all these results together, we conclude that TRPV1 hyperfunction contributes to oxalate-induced renal inflammation. Blunting TRPV1 function attenuates hyperoxaluric nephropathy.